2020
DOI: 10.1002/pmh.1496
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apparently negative personality characteristics on the long‐term outcome of health anxiety: Secondary analysis of a randomized controlled trial

Abstract: Background It is known that personality has an influence on the outcome of mental state disorders, but detailed studies on its long‐term impact are few. We examined the influence of personality status on the 8‐year outcome of health anxiety and its relationship to the effects of cognitive behaviour therapy in a randomized controlled trial. Aims This study aims to examine both the usefulness of the diagnosis of personality disorder and an additional measure of pathological dependence, in predicting the outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…A personality problem can be a personality strength at the same time. In another study of the treatment of health anxiety in medical patients with an adapted form of CBT, those with personality disorder had significantly better outcomes compared with non‐personality disordered patients, and the findings suggested that better adherence to the treatment programme and lower drop‐outs in the personality disordered group (who had prominent anankastic and anxious domain traits) was the main reason for this (Tyrer, Wang, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A personality problem can be a personality strength at the same time. In another study of the treatment of health anxiety in medical patients with an adapted form of CBT, those with personality disorder had significantly better outcomes compared with non‐personality disordered patients, and the findings suggested that better adherence to the treatment programme and lower drop‐outs in the personality disordered group (who had prominent anankastic and anxious domain traits) was the main reason for this (Tyrer, Wang, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows the long-term outcome (8 years) of over 400 patients treated with health anxiety in a randomised controlled trial using a psychological method based on cognitive behavioural therapy. 11 Those with a high degree of dependent personality at baseline had a much better outcome with treatment than others with low degrees of dependence. Quite a few of those with high dependence were men.…”
Section: Recognising and Managing Personality Disordermentioning
confidence: 95%
“…It is also unwise to assume automatically that those with personality problems will fare worse in treatment than others. Figure 2 shows the long‐term outcome (8 years) of over 400 patients treated with health anxiety in a randomised controlled trial using a psychological method based on cognitive behavioural therapy 11 . Those with a high degree of dependent personality at baseline had a much better outcome with treatment than others with low degrees of dependence.…”
Section: Recognising and Managing Personality Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Tyrer et al 14 . present the results of a randomized clinical treatment trial of patients with health anxiety, some of whom met ICD‐11 criteria for PD, whereas others did not.…”
Section: Papers In the Special Issuementioning
confidence: 99%